Pengaruh Model Pembelajaran Berbasis Masalah terhadap Pemahaman Konsep Peserta Didik Kelas VII SMP Negeri 4 Pallangga Kab. Gowa - Hartiwi Aliah Ningsih; Sitti Rahma Yunus; Sitti Saenab; Ratnawaty Maming (Universitas Negeri Makassar, 2022)
This research imed to: (1) To find out how high the level of understanding of the concept of learners after being taught through problem based learning, (2) To find out how high the level of understanding of the concept of learners after being taught through direct learning, (3) To find out whether there is influence of Problem based learning to understanding the concept of students of class VII of SMP Negeri 4 Pallangga Kab.Gowa (Study on the subject matter of temperature and heat materials) academic year 2017/2018. The research method used is Quasi-experiment method using Pretest-Posttest Nonequivalent Control Group Design. The population of this study is the students of class VII of SMP Negeri 4 Pallangga Kab.Gowa in the even semester of the academic year 2017/2018 consisting of ten classes with 120 students. The sample of this research as much as two classes of class VII.1 as experimental class and class VII.2 as a control class selected at random with the assumption that the whole class is homogeneous. Data collection techniques conducted in this study by using research instrument that is concept comprehension test and observation sheet model implementation. The tests used are pretest and posttest in the form of objective tests. The data obtained were processed using descriptive statistical analysis and inferential statistics for both classes. Based on the result of data analysis for experiment class get the average value equal to 34.43 in very high category and control class get average value equal to 32.23 in high. Based on the results of the research, it is found that (1) the level of understanding of the concepts of learners who are taught using problem based learning is very high, (2) the level of understanding of the concepts of learners who are taught using direct learning is high, (3) There is influence problem based learning to the understanding of the concept of students of class VII of SMP Negeri 4 Pallangga Kab.Gowa (Study on the subject matter of temperature and heat materials ) of academic year 2017/2018.